AI-Powered Troubleshooting Co-pilots: Slash Resolution Time and Boost CSAT - Mukul Garg, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
AI co-pilots utilizing Large Language Models (LLMs) and Natural Language Processing (NLP) significantly enhance technical support by analyzing structured (tickets, CSAT) and unstructured (logs, chats) data in real-time to suggest solutions. This article details the data engineering pipelines and AI model integration required, demonstrating through e-commerce and finance case studies reductions in Mean Time to Resolution (MTTR) (35-60%), increases in First Contact Resolution (FCR) (15-25%), and corresponding Customer Satisfaction (CSAT) improvements (10-20 points). The direct link between accelerated, accurate resolutions and higher CSAT is established.
Keywords: AI Troubleshooting; Support Co-pilot; LLM; NLP; Resolution Time; CSAT; Data Pipelines